2007
DOI: 10.1038/sj.ejcn.1602970
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary glycemic index, dietary glycemic load and mortality among men with established cardiovascular disease

Abstract: Background/objectives: In men with established cardiovascular disease, the effect of diets with high glycemic index (GI) and glycemic load (GL) is unknown. We tested the hypothesis that diets with higher GI and GL are associated with increased mortality in men with established cardiovascular disease. Subjects/methods: We measured dietary GI and GL using food-frequency questionnaires in 4617 men, 45-79 years old, with a history of cardiovascular disease. The men were followed for cardiovascular mortality (6-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…Several prospective studies assessing the relationship between dietary GI or GL and cardiovascular disease risk were identified ( Table 9 ). Those reporting on cardiovascular disease mortality [ 77 , 78 ] or on incident cardiovascular diseases (all combined) [ 79 , 80 ], coronary heart disease [ 81 , 82 , 83 , 84 , 85 ], stroke [ 80 , 82 , 85 ], myocardial infarction [ 80 , 86 ], or heart failure [ 87 ] were included herein. Most studies provided risk estimates that were adjusted for dietary factors, age, body mass index, and other potentially confounding factors.…”
Section: Glycemic Index/glycemic Load and Cardiometabolic Disease mentioning
confidence: 99%
See 1 more Smart Citation
“…Several prospective studies assessing the relationship between dietary GI or GL and cardiovascular disease risk were identified ( Table 9 ). Those reporting on cardiovascular disease mortality [ 77 , 78 ] or on incident cardiovascular diseases (all combined) [ 79 , 80 ], coronary heart disease [ 81 , 82 , 83 , 84 , 85 ], stroke [ 80 , 82 , 85 ], myocardial infarction [ 80 , 86 ], or heart failure [ 87 ] were included herein. Most studies provided risk estimates that were adjusted for dietary factors, age, body mass index, and other potentially confounding factors.…”
Section: Glycemic Index/glycemic Load and Cardiometabolic Disease mentioning
confidence: 99%
“…The relationship between dietary GI or GL with incident cardiovascular diseases (all combined) was assessed in a 6-year follow-up of Swedish men 45–79 years of age [ 80 ] and in a subsequent analysis of 4167 participants from the same study with established cardiovascular disease [ 79 ]. Both analyses resulted in no significant associations.…”
Section: Glycemic Index/glycemic Load and Cardiometabolic Disease mentioning
confidence: 99%
“…Because the associations of dietary GI and GL with cardiovascular disease were stronger in overweight then normal weight women in some studies (3, 23) possibly because of a greater prevalence of insulin resistance among overweight women, we tested for variation by body mass index (BMI) and by physical activity, another determinant of insulin sensitivity. We also examined the possibility of interaction of dietary GI and GL with fiber consumption, because dietary GL was associated with survival among men with established cardiovascular disease only in the context of low fiber intake (28). …”
mentioning
confidence: 99%
“…We previously reported that dietary GL was associated with higher mortality in men with existing cardiovascular disease only in the setting of relatively low fiber intake [44]. However, in this population, the association of dietary GI and GL with HF was stronger in women with higher fiber intake, though the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 64%
“…Because previous studies have observed stronger association of dietary GI and GL with cardiovascular disease in overweight participants [12, 13, 31, 32], we tested whether the associations varied by body mass index. In a previous study in a Swedish population, we found that dietary GL was associated increased mortality in men with established cardiovascular disease only in the setting of relatively low fiber consumption [33]. We therefore examined whether the associations of dietary GI and GL with HF varied by fiber intake.…”
Section: Introductionmentioning
confidence: 98%